Agreement between ventilatory thresholds and bilaterally measured vastus lateralis muscle oxygen saturation breakpoints in trained cyclists: Effects of age and performance - Reinpõld, K.; Rannama, I.; Port, K. (Sports, 2024)
This study focused on comparing metabolic thresholds derived from local muscle oxygen saturation (SmO2) signals, obtained using near-infrared spectroscopy (NIRS), with global pulmonary ventilation rates measured at the mouth. It was conducted among various Age Groups within a well-trained cyclist population. Additionally, the study examined how cycling performance characteristics impact the discrepancies between ventilatory thresholds (VTs) and SmO2 breakpoints (BPs).